Research on quantitative measurement method of articular cartilage thickness change based on MR image - Zirun Wang; Liqin Liang (Elsevier, 2020)
In order to study the quantitative measurement method of articular cartilage thickness change based on MR image, 140 patients with no knee joint symptoms and 17 patients with knee joint damage were studied. FLASH, SE and FISP 3 sequences were scanned for all normal knee joints to determine the articular cartilage thickness. 17 patients with knee joint damage were followed up for six months. The thickness of their femoral condyle and femoral trochlea cartilage was measured by FLASH sequence and thickness changes are recorded. The results show that the thickness distribution of normal knee articular cartilage in different parts is not equal, and the thickness of articular cartilage will be gradually thinner in different ages; MR image technique can observe the change of articular cartilage thickness in patients with knee joint damage, reflecting the recovery status of the patient's condition. The results of quantitative measurement of changes in articular cartilage thickness based on MR images are presented herein, and the results are as expected. Experimental data were provided for the clinical treatment of acute knee injury and osteoarthritis. Although there are still some shortcomings in the research process, the research results still provide some reference and guidance for the future exploration of the use of MR images to monitor the condition of arthritis, so this study is a significant research topic.